Peningkatan Performa Ayam Broiler dengan Suplementasi Daun Salam [Syzygium polyanthum (Wight) Walp] Sebagai Antibakteri Escherichia coli - K G Wiryawan; S Luvianti; W Hermana; S Suharti (Media Peternakan, 2007)
The objective of this experiment was to determine the effect of bay leaves (S. polyanthum (Wight) Walp) used in the diet as E. coli antibacteria in improving broiler performances. This experiment used 180 day old chicks (DOC) of Cobb strain which were kept in litter system for five weeks. The experiment used completely randomized design with six treatments and three replications consisting of 10 broilers in each replication. The treatment diets were R0 = control diet, R1 = R0 infected with E. coli, R2 = R1 + 1% bay leaves, R3 = R1 + 2% bay leaves, R4 = R1 + 3% bay leaves, R5 = R1 + antibiotic. The data were analyzed with analysis of variance. The variables observed were feed consumption, body weight gain, final body weight, feed conversion ratio, mortality, and total colony of E. coli in broiler excreta. The results showed that the use of bay leaves up to 3% in the ration increased broiler performance by increasing feed consumption and body weight gain, depressing the number of E. coli in excreta, and reducing mortality compared to the other treatments, but it did not affect the feed conversion ratio. Key words: bay leaves, antibacteria, E. coli, broiler performance